Title: Arctic, Croft, Tigerlily Title Vads Collection: Design Council Slide Collection - Designer: Brockman, Richard Manufacturer: Josiah Wedgwood & Sons Ltd (1974)
Description: Items of ceramic tableware (teapot, milk jug and two plates) with 'Tigerlily'/'Arctic' designs on 'Croft' shape designed by Richard Brockman and made by Josiah Wedgwood & Sons Ltd., 1974.